A New Frontier: The Development and Validation of the Intimate Partner Cyber Abuse Instrument. (August 2022) - Fissel, Erica R.; Graham, Amanda; Butler, Leah C.; Fisher, Bonnie S.
As technology advances, new opportunities for partners to gain power and control in their romantic relationships are readily available. New cyber-based behaviors have slowly garnered scholarly attention, but measurement-related issues have not. We take the logical next steps to (1) develop and validate a comprehensive measure of intimate partner cyber abuse (IPCA) for adults using classical test theory and item response theory and (2) estimate IPCA prevalence rate for a range of relationship types. A sample of 1, 500 adults, currently in an intimate partner relationship, 18 years or older, and living in the United States, completed an online questionnaire about their IPCA experiences within the 6 months prior. Two parameter logistic modeling and confirmatory factor analyses revealed a five-dimensional structure: cyber direct aggression, cyber sexual coercion, cyber financial control, cyber control, and cyber monitoring, with 14.85% of the sample experiencing at least one dimension. These IPCA dimensions were examined for differential functioning across gender identity, race, student status, and relationship type. Collectively, the findings have implications for IPCA measurement and related research, including theoretically derived hypotheses whose findings can inform prevention.